Solvent-assisted thermal reduction of microcrystalline graphene oxide with excellent microwave absorption performance. Issue 28 (24th April 2018) - Liao, Chenbo; Zhu, Xukun; Xie, Wei; Zeng, Fangmei; Yi, Shihe; Cheng, Haifeng; Kuang, Jiacai; Deng, Yingjun; Cao, Taishan
Abstract : Reduced microcrystalline graphene oxide (rGO-M), a novel absorber with high absorption, low reflection and a wide absorption band, was prepared from NMGMs using a solvent-assisted thermal reduction method. Abstract : To prepare a new kind of electromagnetic wave absorber, and improve the processing technology and accessional value of natural microcrystalline graphite minerals (NMGMs), reduced microcrystalline graphene oxide (rGO-M), a novel absorber with high absorption, low reflection and a wide absorption band, was prepared from NMGMs using a solvent-assisted thermal reduction method. Moreover, the as-produced rGO-M with adjustable electrical resistivity can be easily transferred into well distributed bulk materials by freeze-drying technology. These unique structures and compositions make a great contribution to the impedance match, and cause strong conductive loss and various dipole polarization effects which greatly enhance the absorption. Meanwhile, the effective bandwidths below −5 dB and −10 dB are 11.7 GHz and 3.32 GHz respectively, and the reflection loss can reach −42.68 dB. The study will be beneficial to the development of carbon resources and carbon materials research. Besides, it can provide a scientific basis for the further improvement of the comprehensive utilization and the level of deep processing technology of NMGM resources.